2013
DOI: 10.1097/bpb.0b013e32835b2e7f
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in physical examination and gait parameters in normally developing children and adolescents

Abstract: This study aimed to examine the correlations between physical examinations and gait kinematics, and age-related changes in 47 normally developing children. Physical examinations were not found to be significantly correlated with kinematics, except for Thomas and Staheli tests. Unilateral and bilateral popliteal angles decreased significantly by 2.2 and 1.6° per annum, and ankle dorsiflexion with knee extension and 90° flexion decreased significantly by 0.7 and 0.8°. Physical examinations and gait parameters mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
4
8
0
Order By: Relevance
“…This approach is a modification of the original Thomas test, which does not allow hip extension beyond a neutral position [22,23,31]. Our results for hip extension using the modified Thomas test, ensuring a standardized pelvic position with the ASIS aligned over the PSIS, are comparable with the findings of Kilgour et al [1] and Lee et al [16], who reported means of 151 (SD 61) and 11.11 (SD 3.71) using the Staheli test [45] across similar age groups. Our results for hip extension using the modified Thomas test, ensuring a standardized pelvic position with the ASIS aligned over the PSIS, are comparable with the findings of Kilgour et al [1] and Lee et al [16], who reported means of 151 (SD 61) and 11.11 (SD 3.71) using the Staheli test [45] across similar age groups.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This approach is a modification of the original Thomas test, which does not allow hip extension beyond a neutral position [22,23,31]. Our results for hip extension using the modified Thomas test, ensuring a standardized pelvic position with the ASIS aligned over the PSIS, are comparable with the findings of Kilgour et al [1] and Lee et al [16], who reported means of 151 (SD 61) and 11.11 (SD 3.71) using the Staheli test [45] across similar age groups. Our results for hip extension using the modified Thomas test, ensuring a standardized pelvic position with the ASIS aligned over the PSIS, are comparable with the findings of Kilgour et al [1] and Lee et al [16], who reported means of 151 (SD 61) and 11.11 (SD 3.71) using the Staheli test [45] across similar age groups.…”
Section: Discussionsupporting
confidence: 85%
“…As noted in the recent studies of Sankar et al [20] and Lee et al [16], ROM was related to age, with a significant reduction in range observed in the older age groups for most measures (Fig. As noted in the recent studies of Sankar et al [20] and Lee et al [16], ROM was related to age, with a significant reduction in range observed in the older age groups for most measures (Fig.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies have demonstrated that the popliteal angle is increased in children and adolescents. 5 18 The age of the cohorts in these previous studies ranged from 1−5 years. The unilateral popliteal angle with lordosis and an anteriorly tilted pelvis is a measure of functional hamstring contracture, and the bilateral popliteal angle with a loss of lordosis and neutral pelvis is a measure of the true hamstring contracture ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the popliteal angle tends to increase with age in younger populations. 18 However, there are few such studies including both adolescents and adults.…”
Section: Introductionmentioning
confidence: 99%